Transformation of Architecture of Rumoh Aceh: An Encoding Process Through Semiotic - Putra, Riza Aulia; Ekomadyo, Agus Suharjono (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2023)
Rumoh aceh is a Acehnese traditional house which is one of the products and artifacts of the Acehnese culture. Efforts to preserve rumoh aceh often focus on physical aspects or aspects of form that are seen directly. This has led to the discovery of many new buildings that adopt the architectural form of rumoh aceh directly without a more comprehensive elaboration and transformation process. A concerted effort is required to present rumoh aceh architecture in a modern context. Transformation is one of the methods in architectural design to be able to present new ideas that are creative and innovative. The transformation in this paper is obtained through an encoding process that employs a semiotic approach as a method for bridging the rumoh aceh architecture transformation process. The encoding process is carried out by reinterpreting the values of rumoh aceh architecture obtained from previous research. The aim of this paper is to gain knowledge regarding the architectural design process that can present a creation that represents regional culture, in this case to present rumoh aceh architecture in a modern context.